Protection of copyright on the Internet - Кирилюк, Алла Володимирівна; Кирилюк, А. В.; Кирилюк, Алла Владимировна; Kyryliuk, Alla V.; Бааджи, Наталія Пилипівна; Бааджи, Н. П.; Бааджи, Наталия Филипповна; Baadzhy, Nataliia P.; Гонгало, Регіна Францівна; Гонгало, Р. Ф.; Гонгало, Регина Францовна; Honhalo, Rehina F.; et al. (Editorial Primmate S. A. S., 2019)
The problem of improving of legislation in the field of copyright protection is one of the urgent problems facing modern legislation. Due to the rapid development of information and communication technologies, dishonest users have the opportunity to post fragments of other people's creative works on their sites without reference to the author, source of borrowing and without disclosing information about the owners of the site. According to the main international copyright convention, the Berne Convention for the Protection of Literary and Artistic Works (1886), copyright protection covers a wide array of human creativity - all “literary and artistic works.” Due to the process of digitization all these forms of creativity can be transmitted across the Internet and in case of violation of rights to them, a mechanism for their protection should be developed in a modern society. It is concluded that information is transmitted via the Internet mainly in the form of creative works that are object to copyright. Moreover, the implementation of any formalities and the fact of publication of the creative work are not needed. The peculiarities of the legal regime of creative works placed on the Internet, the rights of which are the object of civil protection, were disclosed in the article. The author discloses problems of copyright protection for works posted on the Internet, including the problem of identification of the offender. In the article it is also identified basic ways to protect copyright, such as self-defense and judicial protection. The author examines issues of copyright protection for creative works posted on the Internet. Technical and legal means and methods of protecting the rights of authors are analyzed, which allow effective protection of creative works placed on the Internet both before and after their infringement. In the article it is argued that the protection of interests of copyright entities on the Internet depends to a large extent on the technological means that they use. The evolution of these tools and techniques will diminish the role of copyright as a regulator of civil legal relations on the Internet.

Проблема вдосконалення законодавства у сфері охорони авторського права є однією з актуальних проблем сучасного законодавства. Завдяки стрімкому розвитку інформаційно-комунікаційних технологій недобросовісні користувачі мають можливість розміщувати на своїх сайтах фрагменти чужих творчих робіт без посилання на автора, джерело запозичення та без розголошення інформації про власників сайту. Відповідно до головної міжнародної конвенції про авторське право, Бернської конвенції про охорону літературних і художніх творів (1886), охорона авторського права охоплює широкий спектр людської творчості – усі «літературні та художні твори». Завдяки процесу оцифровки всі ці форми творчості можуть передаватися через Інтернет, і в разі порушення прав на них у сучасному суспільстві має бути розроблений механізм їх захисту. Зроблено висновок, що інформація передається через Інтернет переважно у формі творчих робіт, які є об’єктом авторського права. Причому виконання будь-яких формальностей і факт публікації твору не потрібні. У статті розкрито особливості правового режиму розміщених у мережі Інтернет творчих робіт, права на які є об’єктом цивільного захисту. Автор розкриває проблеми захисту авторських прав на твори, розміщені в мережі Інтернет, зокрема проблему ідентифікації порушника. У статті також визначено основні способи захисту авторського права, такі як самозахист і судовий захист. Автор розглядає питання захисту авторських прав на творчі роботи, розміщені в мережі Інтернет. Проаналізовано техніко-правові засоби та методи захисту прав авторів, які дозволяють ефективно захистити творчі твори, розміщені в мережі Інтернет як до, так і після їх порушення. У статті стверджується, що захист інтересів суб’єктів авторського права в Інтернеті значною мірою залежить від технологічних засобів, які вони використовують. Еволюція цих інструментів і прийомів призведе до зниження ролі авторського права як регулятора цивільних правовідносин в Інтернеті.
Kyryliuk A. Protection of copyright on the Internet / A. Kyryliuk, N. Baadzhy, R. Honhalo, N. Kapustina, L. Galupova // Amazonia Investiga. – Vol. 8. - Issue 24. – Editorial Primmate S. A. S., 2019. – P. 464-470.
Keywords: intellectual property; copyright; related rights; protection of copyright and related rights; Internet; інтелектуальна власність; авторське право; суміжні права; захист авторського права та суміжних прав; Інтернет; Research Subject Categories::LAW/JURISPRUDENCE